Pengaruh Sistem Eksitasi Terhadap Generator Sinkron Tiga Fasa Di Unit 1 PT. PLN Indonesia Power ULPL TA Musi - Aziz Zulhakim; Yanolanda Suzantry Handayani; Irnanda Priyadi (UNIB Press, 2023)
PLN Indonesia Power ULPL TA Musi utilizes the potential energy of water which is then used to drive a turbine connected to a generator rotor. Excitation system plays an important role in controlling the stabil of a generator as a controller and functions to control generator output such as voltage, current and power factor. The excitaton system for all units in the Musi hydroelectric power house uses a brush excitation system. Brush excitation is an excitation with a brush by utilizing the output of the generator itself as the excitation. There are 3 types of generator power, namely active power (MW), reactive power (MVAR), and apparent power (MVA). This data is taken from the daily operaing data of the Musi turbine hydropower unit 1. The highest power factor value is obtained in the early morning of 0,999 Cos  with a reactive power value of 0,5 MVAR to 1,8 MVAR. While the lowestpower factor value is 0,975 Cos  with a reactive power value is 6,2 MVAR. The smaller the reactive power value, the greater the power factor.